Analysis of MSME Marketing Strategies Based on Local Wisdom to Increase Sales - Radityo Suksmaneng Daru; Vera Selviana Adoe; Wiwit Agustina; Dany Luqyana Idris (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the marketing strategies of Micro, Small, and Medium Enterprises (MSMEs) based on local wisdom in increasing sales. Local wisdom is a competitive advantage that can provide added value to products through the use of culture, traditions, and regional potential as a business identity. The study used a qualitative approach with descriptive methods. Data were obtained through in-depth interviews, observations, and documentation of MSMEs who apply elements of local wisdom in their business activities. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques, while data validity was tested through source triangulation, technical triangulation, and member checking. The results show that the implementation of local wisdom-based marketing strategies can increase product appeal, strengthen brand image, and create differentiation that distinguishes MSME products from competitors. The use of digital media combined with storytelling about the product's cultural values has been proven to expand market reach and increase consumer purchasing interest. In addition, branding that emphasizes local identity provides added value to products, thereby increasing customer trust and loyalty. The study also identified several obstacles, including limited digital marketing capabilities, limited business capital, low innovation in product packaging, and the suboptimal use of cultural values as a promotional strategy. Overall, local wisdom-based marketing strategies have had a positive impact on increasing sales, customer numbers, and the competitiveness of MSMEs, while also contributing to the preservation of local culture and empowering the community's economy. Therefore, support from the government, academics, and various stakeholders is needed through training, mentoring, branding strengthening, and digital marketing development so that local wisdom-based MSMEs can develop sustainably.